Model Penguatan Literasi Berbasis Karya untuk Mengembangkan Kemampuan Menulis Siswa Kelas III SDN Landungsari 02: Penelitian - Aisyah Fatikah Basyah; Dinda Lestari; Faiza Rauf; Hartati Arining Rahayu; Beti Istanti Suwandayani (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to describe the improvement of writing skills of third-grade students at SDN Landungsari 02 through the implementation of the Work-Based Literacy Strengthening Model. The study used a qualitative descriptive approach with students and teachers selected purposively as subjects. Data were collected through observation, interviews, documentation, and analysis of students' written works, then analyzed using the Miles and Huberman model. The results showed that work-based literacy, such as writing stories, poems, and pantuns, effectively improved students' writing skills, especially in developing ideas, vocabulary, and composing coherent paragraphs. In addition, this model also increased students' motivation and self-confidence and built a positive literacy culture in the classroom. The successful implementation of this model was supported by consistent implementation, active teacher involvement, and the availability of school facilities.